2017
DOI: 10.24200/sci.2017.5077.1079
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the effect of water to cement ratio on mechanical and durability properties of Nano-silica concretes with Polypropylene fibers

Abstract: In the present paper, the effect of Nano silica on mechanical properties and durability of concrete containing polypropylene fibers has been investigated. Here, the length and length to diameter ratio of used polypropylene fibers were considered to be fixed and equal to 18 mm and 600 respectively and the cement content was 479 kg/m 3 . The effect of fibers and Nano silica in four different percentages for each one at 0.1, 0.2, 0.3 and 0.4 percent by volume for fibers and 3 percent for Nano silica in concrete w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The summary of the aforementioned studies can be shown in Table 5 as the follows: However, some studies conflict with that in terms of the positive effect of polypropylene fibers addition on the concrete resistance to freezing and thawing cycles. These studies reported that the polypropylene fiber reinforced specimens did not display a remarkable alteration in their freezing and thawing performance (Zhang and Li 2013, Rahmani et al 2019, Puertas et al 2003. Chenfei and Di-tao indicated that the concrete resistance against deicer-scaling is made less with the incorporation of polypropylene fibers by volumes (0.1, 0.3, 0.5) %.…”
Section: Frost Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The summary of the aforementioned studies can be shown in Table 5 as the follows: However, some studies conflict with that in terms of the positive effect of polypropylene fibers addition on the concrete resistance to freezing and thawing cycles. These studies reported that the polypropylene fiber reinforced specimens did not display a remarkable alteration in their freezing and thawing performance (Zhang and Li 2013, Rahmani et al 2019, Puertas et al 2003. Chenfei and Di-tao indicated that the concrete resistance against deicer-scaling is made less with the incorporation of polypropylene fibers by volumes (0.1, 0.3, 0.5) %.…”
Section: Frost Resistancementioning
confidence: 99%
“…The reason behind that was the higher porosity of the specimens as a result of fibers content growing. It was reported that the cause for lowering the permeability around 50% with fibers existence is ascribed to the positioning of fibers between the pored interconnectedness passages and their blocking, leading to the elimination of the capillary feature and the penetrability lowers (Rahmani et al 2019). The aforementioned studies can be summarized in Table 1 as the follows: However, there are some studies on water and gas permeability of the polypropylene fiber reinforced concrete that have opposite results to the findings of the above-mentioned studies.…”
Section: Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, very few studies have been focused on the Nano-materials and MPF together. In particular, the effect of NS that will get higher strength (Amin & Abu el-Hassan, 2015;Mustafa et al, 2020;Rahmani et al, 2019;Rashmi & Padmapriya, 2021;Shi et al, 2021;Sridhar et al, 2019;Zhang, Sha, et al, 2021). It may be used in a variety of ways to strengthen structural elements under static and dynamic stress and to minimize cracking and crushing (Rahmani et al, 2019).…”
mentioning
confidence: 99%
“…In particular, the effect of NS that will get higher strength (Amin & Abu el-Hassan, 2015;Mustafa et al, 2020;Rahmani et al, 2019;Rashmi & Padmapriya, 2021;Shi et al, 2021;Sridhar et al, 2019;Zhang, Sha, et al, 2021). It may be used in a variety of ways to strengthen structural elements under static and dynamic stress and to minimize cracking and crushing (Rahmani et al, 2019). The most effective way to improve the mechanical properties of concrete is using NS, which changes the Interfacial Transition Zone (ITZ) between cement paste and aggregate, reduces porosity, increases penetration resistance, and increases the strength of the hardened cement matrix (Akbarpour et al, 2018).…”
mentioning
confidence: 99%